Determination of the Minimum Cell-to-Cell Adhesion Time Using Optical Tweezers in Leukemia and Lymphoma Research - Kamila Duś-Szachniewicz; Sławomir Drobczyński (Methods and Protocols)
Single-cell adhesion assays can be divided into studies on attachment and detachment events, and several methods that enable the characterization of both processes have been established in the past. Due to their low invasiveness, label-free principles, and contactless operation, optical methods are especially beneficial for this purpose. Historically, optical tweezers (OTs) have been used to explore single-cell detachment events, allowing for the precise determination of minute physical forces. However, it has been noted that OTs can also be used to study single-cell attachment dynamics, including the evaluation of minimum cell-to-cell contact times necessary to establish a stable adhesive bond. Here, we provide a step-by-step protocol to effectively evaluate minute changes in the adhesion of single leukemia–lymphoma cells using optical tweezers with low laser intensities. This serves as a valuable in vitro model to determine the effects of physical and chemical factors on the adhesive properties of leukemia–lymphoma (LL) cells.